Duties, responsibilities, and challenges of community health workers: Evidence from a health block of northern Indian province - Ramesh Kumar Rattu; Manoj Kumar; Kavita Sekhri; Ankit Chaudhary (Wolters Kluwer Medknow Publications, 2022)
Introduction: Accredited Social Health Activist (ASHA) worker is a significant frontline health worker that acts as a link between community and health services and helps delivering quality health services to vulnerable section of the society. The present study was conducted with an objective to explore the duties and responsibilities of the ASHA worker along with obstacles faced by them while discharging their duties. Methods: It was a cross-sectional study including 150 ASHA workers of a health block in Himachal Pradesh. Data were collected using a semi-structured questionnaire consisting of six subsections dedicated to different dimensions related to ASHA workers. Results: Majority of ASHAs stated that their job had a positive effect on their social relationships, confidence as well as their physical and mental health. About two-thirds workers failed to fulfill targets due to many activities running simultaneously. About 43.3% felt mental stress during the job and 20.7% workers experienced harassment by hospital staff. About 40% stated that they had received unsatisfactory training. Toilet facility was available for only 59.3% workers and safe drinking water for 64.7% ASHAs. Only 4.7% of ASHAs were satisfied with their monthly income. Conclusion: While ASHAs are working with dedication in the field, still they are experiencing many problems associated with their personal life, community norms, terrain of the workplace, transportation, and organizational issues. The study recommends few amendments as ASHAs being an integral part of Indian health system must be given their due consideration so that the vision of universal health coverage and sustained development can be attained effectively.